Brněnská sídliště a jejich urbanistická struktura - Pecka, Lukáš (Vysoké učení technické v Brně. Fakulta architektury)
Ve městě Brně se nachází v obytných souborech, postavených různou konstrukční technologií, přibližně 70 000 bytů. Urbanistická struktura sídlišť je tedy životním prostředím pro více než třetinu obyvatel města Brna. Práce nabízí ucelený, chronologický přehled realizovaných obytných souborů na území města Brna a zabývá se analýzou jejich urbanistické struktury, s přihlédnutím k okolnostem jejich vzniku.

There are roughly 70 000 flats in the city of Brno in housing estates built of various construction technology. Urban structure of such housing estates is thus a living condition for more than a third of Brno residents. The doctoral thesis offers a cohesive chronological overview of residential complexes in the area of the city of Brno, and deals with an analysis of their urban structure, with consideration of the circumstances of their origin.
Brno Housing estates and their Urban Structure
Keywords: sídliště; obytné soubory; bytové domy; urbanistická struktura; veřejná prostranství; Brno; housing estates; housing; residential complexes; apartement buildings; urban structure; public spaces; Brno